Adjunctive repetitive transcranial magnetic stimulation for adolescents with first-episode major depressive disorder: a meta-analysis - Sun, Chen-Hui; Mai, Jian-Xin; Shi, Zhan-Ming; Zheng, Wei; Jiang, Wen-Long; Li, Ze-Zhi; Huang, Xing-Bing; Yang, Xin-Hu; Zheng, Wei (Frontiers in Psychiatry, 2023)
Objective: This meta-analysis of randomized clinical trials (RCTs) was conducted to explore the therapeutic effects, tolerability and safety of repetitive transcranial magnetic stimulation (rTMS) as an adjunct treatment in adolescents with first-episode major depressive disorder (FE-MDD).Methods: RCTs examining the efficacy, tolerability and safety of adjunctive rTMS for adolescents with FE-MDD were included. Data were extracted by three independent authors and synthesized using RevMan 5.3 software with a random effects model.A total of six RCTs involving 562 adolescents with FE-MDD were included.Adjunctive rTMS was superior in improving depressive symptoms over the control group (standardized mean difference (SMD)=-1.50, 95% confidence interval (CI):-2.16, -0.84; I 2 =89%, p<0.00001) in adolescents with FE-MDD. A sensitivity analysis and two subgroup analyses also confirmed the significant findings.Adolescents with FE-MDD treated with rTMS had significantly greater response (risk ratio (RR)=1.35, 95% CI: 1.04, 1.76; I 2 =56%, p=0.03) and remission (RR=1.35, 95% CI: 1.03, 1.77; I 2 =0%, p=0.03). All-cause discontinuations were similar between the two groups (RR=0.79, 95% CI: 0.32, 1.93; I 2 =0%, p=0.60).No significant differences were found regarding adverse events, including headache, loss of appetite, dizziness and nausea (p=0.14-0.82). Four out of six RCTs (66.7%, 4/6) showed that adjunctive rTMS was more efficacious over the control group in improving neurocognitive function (all p<0.05). 4 Conclusion: Adjunctive rTMS appears to be a beneficial strategy in improving depressive symptoms and neurocognitive function in adolescents with FE-MDD. Higher quality RCTs with larger sample sizes and longer follow-up periods are warranted in the future.